2012
DOI: 10.1002/cphc.201200071
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light Photooxidation of Water to Oxygen at Hybrid TiO2–Polyheptazine Photoanodes with Photodeposited Co‐Pi (CoOx) Cocatalyst

Abstract: A cobalt oxide-based oxygen-evolving cocatalyst (Co-Pi) is photodeposited by visible-light irradiation onto nanocrystalline TiO(2)-polyheptazine (TiO(2)-PH) hybrid photoelectrodes in a phosphate buffer. The Co-Pi cocatalyst couples effectively to photoholes generated in the surface polyheptazine layer of the TiO(2)-PH photoanode, as evidenced by complete photooxidation of water to oxygen under visible-light (λ>420 nm) irradiation at moderate bias potentials. In addition, the presence of the cocatalyst also red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 71 publications
5
76
1
Order By: Relevance
“…Following a similar concept, we have been recently developing photoanodes (figure 1) based on a hybrid absorber layer comprising of nanocrystalline TiO 2 and polyheptazine, "PH", more precisely poly(aminoimino)heptazine or melon, a CN x H y polymeric s-heptazine derivative, also often referred to as "graphitic carbon nitride" or "g-C 3 N 4 " in the literature [22][23][24][25][26]. A remarkable feature of PH is its very high thermal and chemical stability, making it a material of choice for photo(electro)catalytic applications [22,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Following a similar concept, we have been recently developing photoanodes (figure 1) based on a hybrid absorber layer comprising of nanocrystalline TiO 2 and polyheptazine, "PH", more precisely poly(aminoimino)heptazine or melon, a CN x H y polymeric s-heptazine derivative, also often referred to as "graphitic carbon nitride" or "g-C 3 N 4 " in the literature [22][23][24][25][26]. A remarkable feature of PH is its very high thermal and chemical stability, making it a material of choice for photo(electro)catalytic applications [22,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Control experiments were performed in either pure water or a water-methanol mixture under UV irradiation and in the presence of photocatalysts (i.e., pristine TiO2, TiO2−δ or CNT-TiO2−δ-60) without Pt co-catalyst. The protocol for the preparation of electrodes for photocurrent measurements was described elsewhere [42]. Briefly, a suspension containing 100 mg of powder sample in 1 mL of ethanol was sonicated for 15 min and then evenly deposited onto ITO glass by doctor blading using scotch tape as the frame and spacer.…”
Section: Photocatalytic and Photoelectrochemical Measurementsmentioning
confidence: 99%
“…In order to optimize the absorption of visible light, it has been coupled with molecular dye sensitizers [109]. Bledowski and coworkers [117] reported a polyheptazine-coated nanocrystaline TiO 2 in which a CoCat was deposited. This catalyzed water oxidation under visible-light illumination and moderate bias potential and improved photocatalytic water oxidation by photo-excitation with UV light [64,118].…”
Section: Directly Light-driven Water Oxidationmentioning
confidence: 99%
“…The mechanism of this improvement is still debated, however. Bledowski and coworkers [117] suggested that it was the result of the improved photooxidation kinetics in the presence of the CoCat cocatalyst; another alternative is that the passivation of TiO 2 surface states resulted in increased hole lifetime and thus improved energy conversion efficiency [118]. [108] Tungsten oxide (WO 3 ) is another n-type semiconductor (Figure 9.10).…”
Section: Directly Light-driven Water Oxidationmentioning
confidence: 99%